THE DYNAMICS OF THE CHALLENGES OF FEMALE ACADEMICS DURING THE COVID-19 PANDEMIC - Triyuni Soemartono; Dwi Indah Kartika; Tb Adi Satria; David Yama (Moestopo International Review on Social, Humanities, and Sciences, 2022)
The purpose of this study was to analyze the problems of women working in the education sector, because in the era of the COVID-19 pandemic there were many changes, especially women who had multiple burdens. The research was conducted at two universities, Universitas Prof. Dr., Moestopo (Beragama) and Universitas Swadaya Gunung Jati (Unswagati) Cirebon. The research method used is a qualitative research method through a descriptive study approach, with a case study approach at two universities as an empirical investigation effort to explore and analyze the phenomenon of female academics during the Covid-19 pandemic. Informants interviewed female lecturers from two universities in depth (in-depth interview). The results of the research show that female lecturers tend to accept the double burden they experience; female lecturers do not yet have a time table agenda that is implemented properly to ensure that their academic work priorities go well; and the Key to Dexterity of Female Lecturers in the Pandemic Period Although accompanied by strong motivation, several lecturers admitted that they were still having difficulties with the double burden condition which experienced a double burden role, still seeing the importance of the role of the household and placing it as a top priority.